South African physician emigration, return migration, and shared migration, 1991-2017: a registry-based analysis - Joseph Nwadiuko, MD; Ligia Paina, PhD (Elsevier, 2019)
Background: Physician emigration-the so-called brain drain-is a topic of great concern to health workforce planners. South Africa has a high number of physician emigrants, yet there are few registry-based studies that have analysed whether these physicians remain abroad permanently. In this study, we aimed to use a registry-based approach to analyse return migration and shared migration in South African physicians. Methods: We extracted information from registry records about South African trained physicians who had registered in Australia, Canada, New Zealand, the USA, or the UK (ACNUU nations) between 1991 and 2017. We used an attrition-based model to identify non-retiree dropouts from UK, New Zealand, and US registries and cross-referenced with a South African physician registry to determine return migration from these countries. Return migration counts in Canada were derived from secondary data from Canadian Medical Association surveys. Physicians who had active simultaneous registration in South Africa and one other nation were counted as shared migrants. Findings: As of December, 2017, there were 11 224 South African trained physicians actively registered to practise in ACNUU nations, around a third (30·2%) fewer than the peak of 16 095 in 2003. Of these, 3596 (32·0%) held dual active registration (shared migration) in an ACNUU nation and South Africa. In 2017, 5008 physicians met criteria for return migration-that is, 30·1% of all non-retired South African physicians with a history of practising medicine in ACNUU countries. There has been a five-fold drop in emigration rates from South Africa between 1991 and 2017 (from 1·8% to 0·3% per year; UK −88·9%, non-UK −74·2%), negatively correlated with a substantial rise in GDP per capita growth within South Africa in time-adjusted models (-0·36% per $100 increase [p=0·01; 95% CI −0·089 to −0·632]). We noted a temporary increase in return migration between 1995 and 2009 and a simultaneous sustained increase in shared migration. Interpretation: A registry-based approach allows simultaneous assessment of physician emigration, return migration, and shared migration. Our findings of decreasing rates of emigration and increasing return and shared migration rates suggest a mobility transition in medical migration in South Africa. Funding: World Bank.